Clinical Practice Guidelines for Hospital-Acquired Pneumonia and Ventilator-Associated Pneumonia in Adults. Issue 1 (2008) - Rotstein, Coleman; Evans, Gerald; Born, Abraham; Grossman, Ronald; Light, R Bruce; Magder, Sheldon; McTaggart, Barrie; Weiss, Karl; Zhanel, George G
Abstract : Hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) are important causes of morbidity and mortality, with mortality rates approaching 62%. HAP and VAP are the second most common cause of nosocomial infection overall, but are the most common cause documented in the intensive care unit setting. In addition, HAP and VAP produce the highest mortality associated with nosocomial infection. As a result, evidence-based guidelines were prepared detailing the epidemiology, microbial etiology, risk factors and clinical manifestations of HAP and VAP. Furthermore, an approach based on the available data, expert opinion and current practice for the provision of care within the Canadian health care system was used to determine risk stratification schemas to enable appropriate diagnosis, antimicrobial management and nonantimicrobial management of HAP and VAP. Finally, prevention and risk-reduction strategies to reduce the risk of acquiring these infections were collated. Future initiatives to enhance more rapid diagnosis and to effect better treatment for resistant pathogens are necessary to reduce morbidity and improve survival. Erratum to "Clinical Practice Guidelines for Hospital-Acquired Pneumonia and Ventilator-Associated Pneumonia in Adults" dx.doi.org/10.1155/2008/191398